A Model for Minimizing Problems in Salam Financing at Islamic Banks in Indonesia - Waluyo, Bambang; Rozza, Sylvia (International Review of Management and Marketing, 2020)
It has been observed that none of the Islamic banks in Indonesia are involved in salam financing. This research aims to explore the problems faced by Islamic banks in Indonesia in the development of salam-based financing products and efforts to minimize it. The study uses a descriptive qualitative exploratory approach. The method of data collecting is documentation. Data is obtained from scientific journals and websites. The example of problems faced in the operation of salam based financing in Islamic banks are: 1) No capital, 2) Lack of knowledge, 3) Profit oriented, 4) Risk of loss of capital, 5) Unkind characters. The result of this study concludes that to minimize the problems, Islamic banks in Indonesia can: 1) Cooperate with agricultural insurance, 2) Establish a symbiotic relationship, 3) Have a marketing network, 4) Innovate salam products with a hybrid contract, 5) Islamic banks make parallel salam, 6) Islamic banks can expand the object of salam financing, 7) Provide salam financing in groups, 8) establish an agricultural bank, 9) Screen the farmers who should receive the salam financing, 10) Continuous education. It is hoped that Islamic banks can innovate salam products to help improve the welfare of farmers and the community. Keywords: model, problems, financing, parallel salam, screening, education JEL Classifications: A1, M2, O3 DOI: https://doi.org/10.32479/irmm.9149